(untitled) (Global Journal of Human-Social Science, 2016)
The present assignment aims at: 1) critically approaching the skill of listening as it is taught in the Greek State Secondary Education in the framework of teaching English as a foreign language (EFL) in state Junior High Schools. This critical study of the skill of listening is of particular interest since EFL books for use in State Junior High Schools have only been recently introduced by the Greek Pedagogical Institute in Greek Secondary Education and 2) creating an authentic-in nature listening input followed by original tasks made by a teacher of EFL in a State Junior High School so as to be consistent with the criteria that are applicable to the skill of listening in modern Applied Linguistics.